2018
DOI: 10.1186/s40425-018-0383-1
|View full text |Cite
|
Sign up to set email alerts
|

Baseline neutrophil-to-lymphocyte ratio (NLR) and derived NLR could predict overall survival in patients with advanced melanoma treated with nivolumab

Abstract: BackgroundPrevious studies have suggested that elevated neutrophil-to-lymphocyte ratio (NLR) is prognostic for worse outcomes in patients with a variety of solid cancers, including those treated with immune checkpoint inhibitors.MethodsThis was a retrospective analysis of 97 consecutive patients with stage IV melanoma who were treated with nivolumab. Baseline NLR and derived (d) NLR were calculated and, along with other characteristics, correlated with progression-free survival (PFS) and overall survival (OS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
312
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 356 publications
(347 citation statements)
references
References 30 publications
29
312
4
2
Order By: Relevance
“…Our findings directly corroborate those of a recent study by Capone et al examining the outcomes of 97 patients treated with nivolumab stratified by NLR . In that study, which used the same NLR cutoff, a very similar proportion of patients (approximately 25%) demonstrated an elevated baseline NLR, and the baseline NLR was highly prognostic for both OS and PFS.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings directly corroborate those of a recent study by Capone et al examining the outcomes of 97 patients treated with nivolumab stratified by NLR . In that study, which used the same NLR cutoff, a very similar proportion of patients (approximately 25%) demonstrated an elevated baseline NLR, and the baseline NLR was highly prognostic for both OS and PFS.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are consistent with other studies of the NLR in the setting of checkpoint inhibition, which find that an elevated baseline NLR alone does not appear to have sufficient prognostic magnitude to merit withholding PD-1 inhibitor therapy. 14,16,17,19,31 Rather, an elevated NLR may identify a patient population of particular interest for clinical trials testing PD-1 inhibition in combination with additional agents. Our findings directly corroborate those of a recent study by Capone et al examining the outcomes of 97 patients treated with nivolumab stratified by NLR.…”
Section: Discussionmentioning
confidence: 99%
“…To date, some factors that correlate with clinical response to anti-PD-1 agents have been identified. A number of bloodderived factors including high relative eosinophil count and relative lymphocyte count, low dNLR, low LDH and absence of metastasis other than soft-tissue/lung have been associated with better OS in melanoma patients treated with anti-PD-1 agents [33,34], as observed here. In addition, high mutational burden in human tumors, including melanoma, correlates with clinical response to PD-1 inhibitors [35].…”
Section: Discussionsupporting
confidence: 71%
“…Low neutrophil-to-lymphocyte ratio (NLR) and low derived NLR (dNLR) resulted also significantly associated with OS in patients treated with nivolumab ( Table 2 and Additional file 2: Fig. S2), accordingly to our recently published data [34]. Focusing on CD8+ cells subsets, CD8+PD-1+ lymphocytes < 9.8% median frequency (p < 0.009) and CD8+PD-1+CD73+ lymphocytes < 2.3% median frequency (p < 0.001) were significantly associated with OS, whilst the proportion of CD8+T cells positive only to CD73 resulted no significantly associated with OS ( Table 2).…”
Section: Association Of Pre-treatment Cd8+cd73+t Cells Frequency Withsupporting
confidence: 80%
“…According to previous published work, we selected 3, 4, 5 and 4.7 (the median) as the NLR cut-off values. [16][17][18] There was not any significant difference between those values and OS (Table S2b). In this study, we confirmed that NLR at baseline, prior to ipilimumab, was not associated with OS after first sequential ipilimumab administration.…”
Section: Immune Cell Measurements Before and During Treatmentmentioning
confidence: 99%